TRANSFORMASI DIGITAL DALAM MANAJEMEN PENDIDIKAN ISLAM: PELUANG DAN TANTANGAN - Miftahul Jannah; Nurul Shafika; Eka Budi Parsetyo; Syafaatul Habib (Jurnal Manajemen Pendidikan Islam Darussalam (JMPID), 2023)
Digital transformation in Islamic education management offers great opportunities to improve the efficiency, effectiveness, and quality of Islamic education. Some of these opportunities include the use of technology in learning, data management, and curriculum development. However, in adopting digital transformation, there are also challenges that need to be overcome, such as cost, technical expertise, and social and cultural challenges. Therefore, a proper strategy is needed in adopting digital transformation and increasing digital awareness and skills among Islamic education managers. By overcoming challenges and leveraging opportunities, Islamic education management can achieve better effectiveness and efficiency in developing curricula and improving the overall quality of Islamic education.